(untitled) (The Review of Diabetic Studies, 2025)
Respiratory therapists (RTs) play a critical role in optimizing patient outcomes through specialized clinical practices, evidence-based interventions, and technological innovations in respiratory care. This comprehensive review explores the evolution of respiratory therapy, its expanding clinical competencies, and the integration of advanced technologies such as tele-respiratory systems, automated ventilators, and artificial intelligence. A literature search of PubMed, Scopus, and CINAHL from 2016 to 2025 identified studies assessing the effectiveness of RT-led interventions in acute, chronic, and rehabilitative care settings. Findings reveal that RT-driven management reduces the duration of mechanical ventilation, lowers hospital mortality, enhances pulmonary rehabilitation outcomes, and improves patient satisfaction. The review also highlights emerging trends, including predictive analytics for ventilator weaning, remote monitoring for chronic diseases, and cross-disciplinary collaboration for integrated respiratory care. Despite notable progress, challenges such as workforce shortages, training disparities, and unequal access to technology persist. Strengthening professional development, adopting unified standards, and embedding innovation in practice are essential to sustain quality, efficiency, and patient-centered care in respiratory therapy worldwide.